Developing and evaluating of NonRealistic Three-Dimensional (3d-Nr) And Two-Dimensional (2d) talking-head animation courseware - Hamdan Mohd Najib, Mohamad Ali Ahmad Zamzuri, (N/A, 2015)
Developing and evaluating of NonRealistic Three-Dimensional (3d-Nr) And Two-Dimensional (2d) talking-head animation courseware by Hamdan Mohd Najib, Mohamad Ali Ahmad Zamzuri,